Carnistic Colonialism: A Rhetorical Dissection of “Bushmeat” in the 2014 Ebola Outbreak - Muller, S. Marek (Frontiers in Communication, 2021)
This article argues that a fusion of critical animal studies and postcolonial critique affords food systems scholars a richer understanding of Western media narratives regarding a “bushmeat problem” during the 2014 Ebola outbreak. To do so, I perform a rhetorical analysis of expert, journalistic, and editorial texts disseminated through outlets with high economic and/or social capital in North American and Western European countries. My analysis demonstrates three overarching themes in these texts regarding the intersections of bushmeat and Ebola, which I describe as: (1) biosecurity; (2) conservation; and (3) development. By invoking an ethic of anti-speciesism and decoloniality, I not only demonstrate the colonial logics at play in the 2014 Ebola outbreak, but also name an insidious ideology fundamental to food systems discourse in postcolonial contexts: carnistic colonialism.